Conflicting Logics in a Changing Action Space: Challenges Related to Type 1 Diabetes in Work Life. (June 2021) - Overgaard, Mathilde; Christensen, Ulla; Nexø, Mette A.
Well-being at work is important to quality of life. However, reconciling work and diabetes management is often challenging; failing to do so threatens the well-being of people with type 1 diabetes (T1D). We explored the mechanisms underlying diabetes-specific challenges at work using theories of logics, involvement, and action space. Thematic analyses of two data sets, consisting of interviews with adults with T1D ( n = 22) showed that people with T1D experience a conflict between two logics linked to diabetes and work, owing to the contradictory demands of work life and diabetes management. Individuals' ability to lower the priority of work tasks—shifting them from their main to a side involvement so as to properly manage T1D—helps resolve the conflict, as does being able to create an enabling action space for diabetes management at work. These insights can inform interventions targeting the well-being of workers with T1D.